2016
DOI: 10.1007/s10508-016-0718-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Sexual Orientation Microaggression Inventory in Two Diverse Samples of LGBTQ Youth

Abstract: Critical race theory asserts that microaggressions, or low-level, covert acts of aggression, are commonplace in the lives of people of color. These theorists also assert a taxonomy of microaggressions, which includes “microassaults,” “microinsults,” and “microinvalidations.” The theory of microaggressions has been adopted by researchers of LGBTQ communities. This study investigated the three-factor taxonomy as it relates to a diverse sample of LGBTQ youth using the newly developed Sexual Orientation Microaggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 31 publications
5
87
0
Order By: Relevance
“…Swann et al argue that microaggressions “are frequently non-deliberate and unconscious on the part of the actor,” which is in accordance with the concept of dignity attacks (28). We use the term dignity attacks both because dignity and dignity attacks are firmly rooted in the vocabularies of the victims of these attacks (as shown by the widespread explicit mention of dignity issues in the grievances expressed by social movements) and also because there is a well-rooted literature on dignity and its denial in philosophy, social science and in the health sciences.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Swann et al argue that microaggressions “are frequently non-deliberate and unconscious on the part of the actor,” which is in accordance with the concept of dignity attacks (28). We use the term dignity attacks both because dignity and dignity attacks are firmly rooted in the vocabularies of the victims of these attacks (as shown by the widespread explicit mention of dignity issues in the grievances expressed by social movements) and also because there is a well-rooted literature on dignity and its denial in philosophy, social science and in the health sciences.…”
Section: Introductionmentioning
confidence: 90%
“…Other related concepts are “enacted stigma” and “microaggression” (13, 27, 28). In a relatively early definition of enacted stigma (towards people with epilepsy), Jacoby defined the term as follows: “In this dichotomy, enacted stigma refers to episodes of discrimination against people with epilepsy, solely on the grounds of their social unacceptability; whereas felt stigma refers to the shame associated with being epileptic and the fear of enacted stigma.” (29) More recently, a USAID document on HIV/AIDS related discrimination and stigma offers the following definition: “We define discrimination (or enacted stigma) as the negative acts that result from stigma and that serve to devalue and reduce the life chances of the stigmatized.” (30) Enacted stigma thus differs from dignity attacks in that it is purposive and aimed specifically at a given stigmatized characteristic of its target.…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of microaggressions are linked to anxiety and anger caused by stress from repeated exposure to innocuous interactions between victims and aggressors (Bostwick & Hequembourg, 2014). One interaction may be minimally impactful, but repeated attacks can precipitate mental health disorders such as depression and posttraumatic stress disorder (Sue, 2010;Swann, Minshew, Newcomb, & Mustanski, 2016). These psychological consequences can burden day-to-day life for victims by altering their worldview and creating trust issues, leading to a psychological conundrum.…”
Section: Microaggressionsmentioning
confidence: 99%
“…• pathologizing homosexuality and diverse gender expression (promotion of heterosexism, nullifying a person's identity [Swann et al, 2016]); and…”
Section: Microaggressionsmentioning
confidence: 99%
“…Sue and colleagues' microaggression taxonomy has been applied across race, gender, and sexual orientation by themselves (see Sue, 2010b) and others. For example, in the context of microaggressions and sexual orientation, Swann, Minshew, Newcomb, and Mustanski (2016) identified experiences of LGBTQ youth analogous to Sue's (2010) racial microaggression taxonomy: anti-gay attitudes ("microinsults"), heterosexism ("microinvalidations"), and societal disapproval ("microassaults") (p. 1289). Swann et al also identified a factor they labeled "denial of homosexuality" (p. 1289).…”
mentioning
confidence: 99%